2018
DOI: 10.1002/pd.5347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the introduction of the three‐vessel view on the detection rate of transposition of the great arteries and tetralogy of Fallot

Abstract: In this nationally organized prenatal screening program with a quality monitoring system and a uniform protocol, DRs of 82.4% for TGA and 67.7% for ToF were reached after the introduction of the three-vessel view as a mandatory item. The three-vessel view significantly contributes to the detection of these conotruncal anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…In TGA, this blood, with a higher oxygen saturation, is ejected into the pulmonary artery and may cause pulmonary vasodilatation and potential ductal constriction. Increased pulmonary blood flow, pulmonary venous return to the left atrium and left ventricular filling then follows . The percentage of the CCO ejected by the left ventricle increases as a consequence to about 50% …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In TGA, this blood, with a higher oxygen saturation, is ejected into the pulmonary artery and may cause pulmonary vasodilatation and potential ductal constriction. Increased pulmonary blood flow, pulmonary venous return to the left atrium and left ventricular filling then follows . The percentage of the CCO ejected by the left ventricle increases as a consequence to about 50% …”
Section: Discussionmentioning
confidence: 99%
“…Historically, low prenatal TGA detection rates have contributed to a relatively limited knowledge of fetal TGA pathophysiology . With the inclusion of additional views in prenatal screening protocols, the prenatal detection rate of TGA is improving . Fetal cardiologists are required to discuss long‐term postoperative outcomes of TGA more frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Dramatic increases have also been noted for prenatal detection of conotruncal anomalies, including transposition of great arteries (from 44% to 82%) and tetralogy of Fallot (from 44% to 68%) compared with the detections rates antedating the introduction of the 3-vessel view. 19 The introduction of standardised screening programmes has also improved the prenatal detection of renal anomalies. 20 F I G U R E 1 Virtual Prenatal Diagnosis Editors annual meeting 2020, Boston USA, Hertfordshire UK, Leuven Belgium, New York USA, Washington USA, Toronto Canada, Melbourne Australia, Oxford UK As for 3-dimensional (3D) US, several studies and meta-analyses have confirmed that 3D US can improve the diagnostic accuracy of 2D US in the evaluation of facial clefts, craniosynostoses, neural tube defects, cardiac, brain and skeletal anomalies.…”
Section: A Decade Of Fetal Ultrasoundmentioning
confidence: 99%
“…Nationally screening programmes incorporating such recommendations have seen a significant improvement in the detection rates of CHD, with highest detection rates (>93%) for hypoplastic left heart syndrome, other univentricular defects and complex defects 18 . Dramatic increases have also been noted for prenatal detection of conotruncal anomalies, including transposition of great arteries (from 44% to 82%) and tetralogy of Fallot (from 44% to 68%) compared with the detections rates antedating the introduction of the 3‐vessel view 19 . The introduction of standardised screening programmes has also improved the prenatal detection of renal anomalies 20 …”
Section: A Decade Of Fetal Ultrasoundmentioning
confidence: 99%